From Text to Context: Reinterpreting Women’s Inheritance Rights in Modern Family Structures from the Perspective of Social Fiqh - Rahmad Setyawan; Muhammad Asyrofudin; Nur Sholikin; Muhammad Adib Samsudin; Fahlul Ulum Ahmad Adnani (Yayasan Abdurrauf Cendekia Nusantara, 2026)
The transformation of modern family structures, characterized by the increasing role of women as primary economic providers, has raised important questions regarding the continued relevance of the 2:1 inheritance distribution ratio. This provision emerged within a socio-historical context in which men were regarded as the primary providers for the family. This study aims to analyze women’s inheritance rights within modern family structures from the perspective of social fiqh. Methodologically, this study employs a normative legal research design using the analytical framework of social fiqh. Data were collected through library research encompassing primary legal materials, including the Qur’an, hadith, statutory regulations, and judicial decisions; secondary legal materials, consisting of classical and contemporary tafsir literature, works on Islamic inheritance law, and relevant scholarly publications; as well as tertiary legal materials, including legal dictionaries, encyclopedias, and other supporting references. The analysis was conducted through a systematic interpretation of the provisions of Islamic inheritance law by taking into account evolving social realities, maqasid al-Shari’ah, the principles of justice, and public benefit. The findings demonstrate that the rules governing the distribution of inheritance property possess a contextual dimension, thereby permitting reinterpretation in response to changes in family structures and the allocation of maintenance responsibilities. Under certain circumstances, the distribution of inheritance property may be reconstructed on a 1:1 basis, provided that it remains grounded in the principles of justice, public benefit, and the objectives of the Shari’ah. This study contributes to the development of Islamic law that is adaptive, contextual, and responsive to social change. [Perubahan struktur keluarga modern yang ditandai dengan meningkatnya peran perempuan sebagai penopang ekonomi keluarga menimbulkan pertanyaan mengenai relevansi ketentuan pembagian warisan dengan rasio 2:1. Ketentuan tersebut lahir dalam konteks sosial yang menempatkan laki-laki sebagai penanggung jawab nafkah keluarga. Penelitian ini bertujuan untuk menganalisis hak waris perempuan dalam struktur keluarga modern perspektif fikih sosial. Secara metodologi, penelitian ini merupakan penelitian hukum normatif dengan kerangka analisis fikih sosial. Data diperoleh melalui studi kepustakaan yang meliputi bahan hukum primer berupa al-Qur’an, hadis, peraturan perundang-undangan, dan putusan pengadilan; bahan hukum sekunder berupa kitab tafsir klasik dan kontemporer, literatur fikih mawaris, serta karya ilmiah yang relevan; dan bahan hukum tersier berupa kamus hukum, ensiklopedia, serta referensi pendukung lainnya. Analisis dilakukan melalui penafsiran sistematis terhadap ketentuan hukum kewarisan Islam dengan mempertimbangkan perkembangan realitas sosial, maqasid as-Syari’ah, prinsip keadilan, dan kemaslahatan. Hasil penelitian menunjukkan bahwa ketentuan pembagian harta warisan memiliki dimensi yang kontekstual, sehingga terbuka untuk melakukan reinterpretasi sesuai dengan perubahan struktur dan tanggung jawab nafkah dalam keluarga. Dalam kondisi tertentu, pembagian warisan dapat direkonstruksi menjadi 1:1 sepanjang tetap berlandaskan prinsip keadilan, kemaslahatan, dan tujuan syariat. Penelitian ini berkontribusi pada pengembangan hukum Islam yang adaptif, kontekstual, dan responsif terhadap perubahan sosial.]